Towards vertical spatial equity of urban facilities: An integration of spatial and aspatial accessibility - Fajle Rabbi Ashik; Sadia Alam Mim; Meher Nigar Neema (Journal of Urban Management, 2020)
To ensure adequate access to urban facilities, it is important for urban planners to achieve equity in the geographical arrangement of such facilities. For the evaluation of vertical spatial equity in the geographical organization of urban facilities, there is a requirement to examine whether and to what degree the variation in spatial accessibility to urban facilities corresponds to the variation in aspatial accessibility for such facilities. While no studies so far measure vertical spatial equity in accordance with 'need' and 'demand' based approaches of equity with a focus on both spatial and aspatial accessibility. Therefore, this paper attempts to measure an integrated spatial accessibility index for the evaluation of geographic variation in spatial accessibility to urban facilities, and then, seeks to integrate spatial accessibility and aspatial accessibility in one framework to evaluate vertical spatial equity in the geographical arrangement of urban facilities. This paper measures integrated spatial accessibility index for urban facilities following the concept of 2SFCA method incorporating supply and demand for urban facilities, the travel distance or time that users are willing to cover to reach such facilities, and the interaction of residents across geographic boundaries. Aspatial accessibility to urban facilities is defined through demographic-demand index and social-need index for those facilities. Spearmen correlation coefficient, spatial analysis models (local spatial autocorrelation in this case), and overlay are used to assess the association between spatial accessibility and aspatial accessibility to urban facilities. The results indicate there exists a variation (inequality) in spatial accessibility to urban facilities in the case study area (DCC). Urban facilities are inequitably distributed within DCC, as high-social-need areas and high-demographic-demand areas have low spatial accessibility to such facilities. These areas should be prioritized in distributing urban facilities in the future, and thus, it can help urban planners to achieve an equitable distribution of urban facilities.
Keywords: 710; 2SFCA; Aspatial accessibility; Spatial accessibility; Spatial equity; Urban facilities